Post-COVID, neurosurgical interventions in rhinocerebral mucormycosis, an institutional experience - Samrendra Kumar Singh; Dhananjay Kumar; Brajesh Kumar; Brajesh Kumar; Niraj Kanaujia; O. P. Gupta; K. M. Jha; Rakesh Kumar Singh (Wolters Kluwer -Medknow Publications, 2022)
Objective: Mucormycosis is an opportunistic, fungal infection, often lethal fungal infection which occurs in immunocompromised patients. However, in this second phase of COVID-19, we faced many post-COVID mucormycosis cases at our institution, IGIMS, Patna. We present our experience in eight patients with this condition who underwent neurosurgical interventions. Patients and Methods: A prospective study for eight patients underwent neurosurgical interventions for rhinocerebral mucormycosis. All cases were operated by same surgeons from ENT and Neurosurgery. Results: Total 42 patients referred for neurosurgical opinion, out of that eight patients taken for neurosurgical interventions. Out of 8, seven patients had COVID reverse transcription-polymerase chain reaction (RT-PCR) positive and treated with steroid and oxygen inhalation and one patient had fever but COVID RT-PCR was negative and treated at home with oxygen cylinder. All of them were treated with either liposomal amphotericin B/amphotericin B or oral posaconazole. Sinus surgery was performed in all eight patients by ENT surgeons, two underwent orbital exenteration by eye surgeon, five patients underwent open craniotomy for cerebral infection while in two patients, cerebral exploration done endoscopically. Six patients survived, while two patients died. Conclusion: Patients with rhino-cerebral mucormycosis spreading outside the sinonasal cavity to the base of brain can be treated successfully to some extent by neurosurgical interventions.